(untitled) (Global Journal of Science Frontier Research, 2021)
This research has the title "To Know to recover; environmental classroom: Birth of Acuaparal water ", this work was carried out with rural students of the eighth and ninth grades of the Novilleros Departmental Educational Institution, located in the municipality of Caparrapí, Cundinamarca, in the basin of the Magdalena Basin, through this strategy it was sought sensitize the children of this territory to the wealth and at the same time the fragility of their environment.